Study of nano cellulose-based membrane tailorable biodegradability for use in the packaging application of electronic devices. (December 2022) - Konganapuram Narasimma Bharathi, Sri Saravana; Adiga, Varun; Khasnabis, Sutripto; Nath, Bidisha; Khan, Nadeem A.; Ramamurthy, Praveen C.
Abstract: With a growing demand for packaging materials and witnessing many landfills and huge garbage islands floating in the Pacific oceans, the need for an alternative material such as bio-degradable plastics has risen. Cellulose-based materials are already in use in several packaging industries. Nanocellulose, a processed cellulose with a specific nanostructure, have several advantages such as high specific strength, modulus, high surface area and unique optical properties. By varying the crosslinking percentages, the kinetics of degradation can be tailored. In this work, extracted cellulose from sugarcane bagasse was hydrolyzed to obtain nanocellulose, which was used to fabricate packaging films (membrane) with PVA as matrix and nanocellulose. Variations of PVA and nanocellulose loadings, and crosslinking agent ratios. In the fabricated films were investigated for chemical, mechanical, optical, thermal, and topographical properties. Results from the degradation tests under appropriate physically simulated environments have suggested that the crosslinking has enhanced the mechanical properties, extent of degradation was dependent on percentages of crosslinking. A real-world device packaging application was demonstrated by encapsulation of perovskite solar cells with the fabricated nanocellulose film revealed that the lifetime of the devices improved which might be indicative of the film having lower permeability for oxygen and moisture. Graphical abstract: Image 1 Highlights: Utilization of Agricultural residues for packaging applications. Biodegradable cellulose-based materials used for device packaging. Extraction and isolation of nanocellulose from sugarcane bagasse. Nanocellulose was crosslinked to tailor mechanical and degradative behavior. Perovskite solar cell encapsulated with nanocellulose film showed extended stability.